Preparation method of high-rate and high-sphericity-degree lithium iron phosphate positive electrode material
By adding a fluorine source to the lithium iron phosphate material and performing neutralization/metalysis reaction, high-magnification and high spherical lithium iron phosphate composite cathode material is prepared in combination with electrospinning technology, which solves the shortcomings of existing materials in terms of compaction density and rate performance, and achieves high energy density and good electrochemical performance.
Patent Information
- Application Number
- CN202411706435.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing lithium iron phosphate positive electrode materials have shortcomings in improving the compaction density and rate performance of the material, and cannot have good electrochemical properties and high energy density at both normal and low temperatures.
By adding a fluorine source to the lithium iron phosphate material and performing a neutralization/metalysis reaction, a lithium fluoride-doped slurry is obtained, and then a fibrous material is produced by electrospinning technology. After drying and high-temperature calcination, a high-magnification and high-spherical lithium iron phosphate composite cathode material is obtained.
The uniform doping of fluoride ions and lithium fluoride coating are achieved, which improves the rate performance and sphericality of the material, enhances the transfer rate of lithium ions, and thus improves the energy density and electrochemical performance of the material.
Smart Images

Figure CN119581522A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a method for preparing a positive electrode material for a lithium ion secondary battery, and specifically relates to a method for preparing a high-rate and high-sphericity lithium iron phosphate composite positive electrode material. Background Art
[0002] With the rapid development of renewable energy industries such as solar energy, wind energy, wave energy and tidal energy, effective energy storage technology has become the focus of research and development in recent years. Since its successful commercial application in the early 1990s, lithium-ion batteries have developed rapidly. Lithium iron phosphate materials have attracted widespread attention in the market, especially in the fields of electric vehicles and electrochemical energy storage, due to their low price, non-toxicity, environmental friendliness, high safety performance and long life. However, lithium iron phosphate materials still have disadvantages such as poor electronic / ionic conductivity, low tap density, and poor high current density charge and discharge capacity, which hinders the application of lithium iron phosphate batteries in high energy density and high rate performance requirements.
[0003] One of the main ways to achieve high energy density is to increase the compaction density of lithium iron phosphate powder. The primary particles are grown by reducing the carbon content and increasing the calcination temperature, thereby improving the compaction of the powder. However, due to the growth of particles, the electrochemical performance will deteriorate sharply, and the discharge capacity and coulombic efficiency will decrease. In terms of improving high-rate performance, ion doping and nano-grinding to reduce particle size can improve the material rate performance to a certain extent, but at the same time it will reduce the compaction density of the material, making lithium iron phosphate unable to meet the needs of high-energy-density batteries.
[0004] Patent CN 109904423A discloses a method for preparing a fluorine ion doped and lithium fluoride coated lithium iron phosphate positive electrode material, characterized in that: a mixture of lithium hexafluorophosphate and lithium iron phosphate is added to deionized water, stirred and dried, and then placed in a muffle furnace for calcination at 300-400°C to obtain the final product. This method improves the lithium ion conductivity rate to a certain extent, but the degree of fluorine ion doping and the uniformity of lithium fluoride coated lithium iron phosphate need to be improved, and the improvement in energy density is limited. Patent CN 101388459B discloses a method for preparing a lithium iron phosphate composite positive electrode material, characterized in that: the lithium iron phosphate obtained by a high-temperature solid phase synthesis method is heated with fluxes NaPO3F and LiPO3F for secondary granulation. This method improves the tap density of lithium iron phosphate, but does not have a good improvement in rate performance. Patent CN 104743537A discloses a method for preparing a high-rate lithium iron phosphate / carbon composite positive electrode material, which is characterized by preparing ferrous phosphate through ferrous sulfate with a lamellar structure, and then preparing ferric phosphate, and finally obtaining a lamellar lithium iron phosphate / carbon composite positive electrode material. The positive electrode material obtained by this method has the characteristics of large initial charge and discharge specific capacity, long cycle life, and excellent rate performance, but at the same time, due to the lamellar structure, the compaction density is not high.
[0005] In summary, the existing lithium iron phosphate preparation method cannot simultaneously improve the material's compaction density and rate performance, so that the material cannot have good electrochemical properties and high energy density at both room temperature and low temperature; therefore, providing a preparation method for lithium iron phosphate positive electrode material with both compaction and rate performance is of great significance to the research and development of lithium-ion batteries. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention provides a method for preparing a high-rate and high-sphericity lithium iron phosphate positive electrode material. The specific technical scheme is as follows: A method for preparing a high-rate, high-sphericity lithium iron phosphate positive electrode material, characterized in that the specific steps are as follows: (1) Weighing iron phosphate and lithium source in a certain proportion and dispersing them in pure water, and mixing and sand-grinding to obtain slurry A; (2) Under stirring conditions, a small amount of fluorine source is added to slurry A, and after a period of reaction, a lithium fluoride-doped slurry B is obtained; (3) Under stirring conditions, an organic carbon source is added to the slurry B to obtain an electrospinning solution C. The fibrous material obtained by electrospinning is dried and calcined at high temperature to obtain a high-rate and high-sphericity lithium iron phosphate composite positive electrode material.
[0007] Furthermore, in step (1), the iron-to-phosphorus molar ratio of the ferric phosphate is 0.95 to 0.99.
[0008] Furthermore, in step (1), the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium chloride, and the molar ratio of the lithium source to the iron source is 1.02 to 1.1.
[0009] Furthermore, in step (1), the primary particle size D of the slurry A is 50 =250~500 nm, solid content is 30~50%.
[0010] Furthermore, in step (2), the fluorine source is one or more of hydrofluoric acid, ammonium fluoride and ferric fluoride.
[0011] Furthermore, in step (2), the fluorine source is used in an amount with a molar ratio of fluorine atoms to lithium atoms of 0.01 to 0.05:1.
[0012] Furthermore, in step (2), the stirring reaction time is 0.5 to 5 h, and the reaction type is neutralization method or double decomposition method.
[0013] In step (2), the particle size can be controlled by ball milling during the reaction process. The ball milling is performed at a dynamic frequency of 30-45 Hz for 10-30 minutes to ensure that the particle size is 80-150 nm, and more preferably, the particle size is between 80-100 nm.
[0014] The dynamic frequency refers to ball milling at 30 Hz-35 Hz for 3-5 min, further ball milling at 40-45 Hz for 3-5 min, and then ball milling at 30 Hz-35 Hz for 3-5 min.
[0015] Furthermore, in step (3), the organic carbon source is one or more of PEG2000, PEG4000, PEG6000, and PEG8000, and the amount used is based on the carbon content of the final product being 2 to 4 wt%.
[0016] Furthermore, in step (3), the electrospinning parameters are: the spinning voltage is 3KV-20KV; and the solution feeding rate is controlled to be 0.1-20 mL / h.
[0017] Furthermore, in step (3), the drying temperature is 60-100°C.
[0018] Furthermore, in step (3), the protective atmosphere is at least one of nitrogen, argon and hydrogen.
[0019] Furthermore, in step (3), the calcination temperature of the electrospinning stock solution C is 500-750° C.; and the calcination and heat preservation time of the electrospinning stock solution C is 6-12 h.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The lithium fluoride obtained by neutralization / metathesis reaction of the lithium source and the fluorine source is evenly dispersed in the sand-milled slurry, and the precursor is obtained by electrostatic spinning, and sintering to obtain a lithium iron phosphate composite material uniformly doped with fluoride ions / coated with lithium fluoride; 2. During the sintering process, lithium fluoride acts as a flux to reduce the calcination temperature and increase the sphericity of lithium iron phosphate, which is conducive to the formation of small-particle, highly spherical iron phosphate; 3. Fluoride ion doping weakens the Li-O bonding, which is beneficial to the deintercalation of lithium ions during charging and discharging. At the same time, lithium fluoride coating can increase the migration rate of lithium ions, thereby improving the rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the sample of Example 1 of the present invention.
[0022] Figure 2 This is a scanning electron microscope image of the sample of comparative example 1 of the present invention.
[0023] Figure 3 1 and 2 are discharge curves of a half-cell made from the lithium iron phosphate composite material obtained in Example 1 of the present invention at different rates (0.1, 1, 3, 5 and 10 C). DETAILED DESCRIPTION
[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0026] Example 1 Weigh 15 g of iron phosphate (Fe / P=0.97) and 7.6 g of lithium carbonate, use water as the ball milling medium, and obtain a particle size D 50 =~270nm, slurry A1 with 38% solid content; Under stirring conditions, 0.75 g of hydrofluoric acid (50 wt%) was added to the slurry A1. After 0.5 h of reaction, 2.1 g of PEG6000 was added and the stirring was continued for 0.5 h to obtain the lithium fluoride-doped slurry B1. During the reaction, the slurry was ball-milled, and the ball-milled slurry was ball-milled at 30 Hz-35 Hz for 5 min, further ball-milled at 40-45 Hz for 5 min, and then ball-milled at 30 Hz-35 Hz for 5 min to achieve particle size control between 80-100 nm. The slurry B1 is electrospun and dried to obtain the precursor C1; the electrospinning parameters are: the spinning voltage is 10KV; the solution feeding rate is controlled to be 10 mL / h, and the drying temperature is 80°C; The precursor C1 was placed in a tubular furnace, calcined at a temperature of 600 °C for 8 h in an inert nitrogen atmosphere, and cooled as the furnace to obtain a fluorine-doped lithium iron phosphate lithium fluoride / carbon positive electrode material.
[0027] Example 2 Same as Example 1, except that the fluorine source is ammonium fluoride.
[0028] Example 3 Same as Example 1, except that the carbon source is PEG2000.
[0029] Example 4 Same as Example 1, except that the amount of hydrofluoric acid used is adjusted to 0.375 g.
[0030] Comparative Example 1 Weigh 15 g of iron phosphate (Fe / P=0.97) and 7.6 g of lithium carbonate, use water as the ball milling medium, and obtain a particle size D 50 =~270nm, slurry A11 with 38% solid content; Under stirring conditions, 2.1 g of PEG6000 was added and stirring was continued for 0.5 h to obtain slurry B11; during the stirring process, the slurry was ball-milled, and the ball-milling slurry was ball-milled at 30 Hz-35 Hz for 5 min, further ball-milled at 40-45 Hz for 5 min, and then ball-milled at 30 Hz-35 Hz for 5 min to achieve a particle size control between 80 and 100 nm; The slurry B11 is electrospun and dried to obtain the precursor C11; the electrospinning parameters are: the spinning voltage is 10KV; the solution feeding rate is controlled to be 10 mL / h, and the drying temperature is 80°C; The precursor C11 was placed in a tubular furnace, calcined at 600°C for 8 h in an inert nitrogen atmosphere, and cooled to obtain a lithium iron phosphate / carbon positive electrode material.
[0031] Comparative Example 2 Weigh 15 g of iron phosphate (Fe / P=0.97) and 7.6 g of lithium carbonate, use water as the ball milling medium, and obtain a particle size D 50 =~270nm, slurry A22 with 38% solid content; Under stirring conditions, 0.75 g of hydrofluoric acid (50 wt%) was added to the slurry A22. After 0.5 h of reaction, 2.1 g of PEG6000 was added and the stirring was continued for 0.5 h to obtain the lithium fluoride-doped slurry B22. During the reaction, the slurry was ball-milled at 40-45 Hz for 15 min. The slurry B22 is electrospun and dried to obtain the precursor C22; the electrospinning parameters are: the spinning voltage is 10KV; the solution feeding rate is controlled to be 10 mL / h, and the drying temperature is 80°C; The precursor C22 was placed in a tubular furnace and calcined at a temperature of 600 °C for 8 h in an inert nitrogen atmosphere. As the furnace cooled, a lithium fluoride / carbon positive electrode material of fluorine-doped lithium iron phosphate was obtained.
[0032] Preparation of button cells The positive electrode material prepared in the embodiment and the comparative example was mixed with the conductive active material SP and the binder PVDF in a ratio of 90:5:5 to form a slurry, and then evenly coated on an aluminum foil to prepare a positive electrode sheet. A high-purity lithium sheet was selected as the negative electrode, the separator was Celgard 2400, and the electrolyte was 1 mol / L LiPF6 dissolved in a mixed solvent of EC and DMC (volume ratio of 1:1). The CR2032 button battery was assembled in a vacuum glove box and then subjected to electrochemical testing.
[0033] Rate performance test The prepared button battery was charged at 0.1C in the voltage range of 2-3.75V at 25°C, and discharged at rates of 0.1C, 1C, 3C, 5C, and 10C, respectively, to obtain the discharge capacity of the battery at different rates. The results are shown in Table 1.
[0034] Table 1: Discharge capacity of various lithium iron phosphate materials at 0.1C, 1C, 3C, 5C, and 10C
[0035] As can be seen from Table 1, the lithium iron phosphate prepared in Example 1 has good rate performance. Compared with Example 1, Example 2 uses ammonium fluoride instead, resulting in a decrease in rate performance, mainly because the change of the fluorine source leads to a poor effect of the reaction doping; Example 3 uses PEG2000 as an organic carbon source, which has different solubility and viscosity in the medium, resulting in a decrease in the electrochemical performance of the lithium iron phosphate; Example 4 reduces the doping amount of the fluorine source, resulting in a decrease in effective doping, which in turn leads to a decrease in rate performance.
[0036] In comparative example 1, without adding fluorine source, the rate performance of lithium iron phosphate obtained is poor. Figure 1 and Figure 2 It can be seen that after high-temperature sintering, the lithium fluoride-doped precursor obtains a lithium iron phosphate composite material with higher sphericity. The results of Comparative Example 2 show that the different ball milling parameters during the ball milling process affect the final rate performance of lithium iron phosphate, which is mainly caused by the difference in ball milling particle size and morphology.
[0037] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.
Claims
1. A method for preparing a high-rate, high-sphericity lithium iron phosphate positive electrode material, characterized in that: The specific steps are as follows: (1) Weighing iron phosphate and lithium source in a certain proportion and dispersing them in pure water, and mixing and sand-grinding to obtain slurry A; (2) Under stirring conditions, a small amount of fluorine source is added to slurry A, and after a period of reaction, a lithium fluoride-doped slurry B is obtained; (3) Under stirring conditions, an organic carbon source is added to the slurry B to obtain an electrospinning solution C. The fibrous material obtained by electrospinning is dried and calcined at high temperature to obtain a high-rate and high-sphericity lithium iron phosphate composite positive electrode material.
2. The preparation method according to claim 1, characterized in that: In step (1), the iron-to-phosphorus molar ratio of the ferric phosphate is 0.95 to 0.99; The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium chloride, and the molar ratio of the lithium source to the iron source is 1.02-1.
1.
3. The preparation method according to claim 1, characterized in that: In step (1), the primary particle size D of the slurry A is 50 =250~500 nm, solid content is 30~50%.
4. The preparation method according to claim 1, characterized in that: In step (2), the fluorine source is one or more of hydrofluoric acid, ammonium fluoride and ferric fluoride; The fluorine source is used in an amount where the molar ratio of fluorine atoms to lithium atoms is 0.01 to 0.05:1; The stirring reaction time is 0.5 to 5 h.
5. The preparation method according to claim 1, characterized in that: In step (2), the particle size can be controlled by ball milling during the reaction process. The ball milling is performed at a dynamic frequency of 30-45 Hz for 10-30 minutes to ensure that the particle size is 80-150 nm, and more preferably, the particle size is between 80-100 nm.
6. The preparation method according to claim 5, characterized in that: The dynamic frequency refers to ball milling at 30 Hz-35 Hz for 3-5 min, further ball milling at 40-45 Hz for 3-5 min, and then ball milling at 30 Hz-35 Hz for 3-5 min.
7. The preparation method according to claim 1, characterized in that: In step (3), the organic carbon source is one or more of PEG2000, PEG4000, PEG6000, and PEG8000, and the amount used is based on the carbon content of the final product being 2 to 4 wt%.
8. The preparation method according to claim 1, characterized in that: In step (3), the electrospinning parameters are: the spinning voltage is 3KV-20KV; the solution feeding rate is controlled to be 0.1-20 mL / h; and the drying temperature is 60-100°C.
9. The preparation method according to claim 1, characterized in that: In step (3), the protective atmosphere is at least one of nitrogen, argon and hydrogen; The calcination temperature of the electrospinning stock solution C is 500-750° C.; the calcination and heat preservation time of the electrospinning stock solution C is 6-12 h.
Citation Information
Patent Citations
Preparation of ferric phosphate composite positive pole
CN101388459B
Preparation method for lithium iron phosphate / carbon composite positive material with high multiplying power
CN104743537A
Preparation method of fluorine ion doped and lithium fluoride coated lithium iron phosphate positive electrode material
CN109904423A
Fluorinion-doped lithium iron phosphate material and preparation methods thereof
CN102024951A
Lithium iron phosphate material for lithium ion power battery, and preparation method thereof
CN104409688A
Cited By
High-temperature-resistant low-iron-dissolution lithium iron phosphate material as well as preparation method and application thereof
CN120664513A
Lithium iron phosphate positive electrode material and preparation method and application thereof
CN122000321A